2020
DOI: 10.1186/s12906-020-02981-w
|View full text |Cite
|
Sign up to set email alerts
|

Cell metabolomics to study the function mechanism of Cyperus rotundus L. on triple-negative breast cancer cells

Abstract: Background: Triple-negative breast cancer (TNBC) is a kind of malignant tumor with higher recurrence and metastasis rate. According to historical records, the dry rhizomes Cyperus rotundus L. could be ground into powder and mixed with ginger juice and wine for external application for breast cancer. We studied the effect of the ethanol extract of Cyperus rotundus L. (EECR) on TNBC cells and found its' apoptosis-inducing effect with a doserelationship. But the function mechanism of EECR on TNBC is still mysteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 44 publications
(49 reference statements)
0
10
0
Order By: Relevance
“…[83] Besides, Yu et al adopted cell metabolomics to study the anticancer mechanism that EECR induced apoptosis by breaking the balance between ATP-production and ATP-consumption. [84] The lycopene-rich extracts obtained from red guava fruit can induce apoptosis in estrogen receptorpositive breast cancers. Yu et al studied the anticancer activity of two extract types from red guava fruit, total extracts, and smaller molecular weight (< 30 kDa) extracts (LMW extracts).…”
Section: Natural Extracts With Anti-tnbc Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…[83] Besides, Yu et al adopted cell metabolomics to study the anticancer mechanism that EECR induced apoptosis by breaking the balance between ATP-production and ATP-consumption. [84] The lycopene-rich extracts obtained from red guava fruit can induce apoptosis in estrogen receptorpositive breast cancers. Yu et al studied the anticancer activity of two extract types from red guava fruit, total extracts, and smaller molecular weight (< 30 kDa) extracts (LMW extracts).…”
Section: Natural Extracts With Anti-tnbc Activitiesmentioning
confidence: 99%
“…When the autophagy inhibitor 3‐methyladenine (3‐MA) was treated in TNBC cells, it could increase EECR sensitivity [83] . Besides, Yu et al adopted cell metabolomics to study the anticancer mechanism that EECR induced apoptosis by breaking the balance between ATP‐production and ATP‐consumption [84] …”
Section: Natural Extracts With Anti‐tnbc Activitiesmentioning
confidence: 99%
“…With the aid of metabolomics, a study recently reported that Cyperus rotundus likely induced apoptosis in TNBC cells by causing an arrest of aerobic glycolysis and increasing the pathways of ATP-consumption like amino acids metabolism, fatty acid metabolism, riboflavin metabolism, and purine metabolism, consequently leading to ATP depletion and cell death [134]. These altered metabolic profiles can serve as a basis for further hypothesis formulation in mechanistic follow-up studies to assess its effects on some key players (enzymes, protein) in these metabolic pathways.…”
Section: Cyperus Rotundus Linnaeusmentioning
confidence: 99%
“…Compared with the tissues or organisms, cell metabolomics has obvious advantages such as lower costs, better stability and reproducibility, fewer ethical issues, among others ( Chrysanthopoulos et al, 2010 ; Cuperlović-Culf et al, 2010 ). In the past few years, cell metabolomics has been used for revealing the therapeutic mechanisms underlying the use of herbs alone or TCM formulae in diseases ( Sun et al, 2018 ; Zhang et al, 2019 ; Ma et al, 2020 ). The major analytical techniques in metabolomics are nuclear magnetic resonance (NMR) spectroscopy, gas chromatography–mass spectrometry (GC-MS), capillary electrophoresis–mass spectrometry (CE-MS), and liquid chromatography–mass spectrometry (LC-MS).…”
Section: Introductionmentioning
confidence: 99%